A comparative analysis of the antioxidant activity of Kalanchoe juices; Russian Journal of Bioorganic Chemistry; Vol. 40, iss. 7 - Sazhina N. N.; Lapshin P. V.; Zagoskina N. V.; Korotkova E. I. Elena Ivanovna; Misin V. M. (2014, 2014)
Title screen